2014
DOI: 10.1016/j.cca.2013.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Establishing benchmarks and metrics for disruptive technologies, inappropriate and obsolete tests in the clinical laboratory

Abstract: Benchmarks and metrics related to laboratory test utilization are based on evidence-based medical literature that may suffer from a positive publication bias. Guidelines are only as good as the data reviewed to create them. Disruptive technologies require time for appropriate use to be established before utilization review will be meaningful. Metrics include monitoring the use of obsolete tests and the inappropriate use of lab tests. Test utilization by clients in a hospital outreach program can be used to mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, like many other tests, it has reached the end of its useful life and needs to be retired along with other tests, such as bleeding time, erythrocyte sedimentation rate, hemosiderin cells in urine, and prostatic acid phosphatase. 10,11 Troponins T and I are more cardiac specific than CK-MB and have been shown to be sensitive and specific markers for myocardial injury in general and ACS in particular. [12][13][14][15] Immunoassays for troponin have been adapted for point-of-care testing and have been deployed in emergency departments; however, given that even the point-of-care test is of moderate complexity, not all institutions have adopted this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…However, like many other tests, it has reached the end of its useful life and needs to be retired along with other tests, such as bleeding time, erythrocyte sedimentation rate, hemosiderin cells in urine, and prostatic acid phosphatase. 10,11 Troponins T and I are more cardiac specific than CK-MB and have been shown to be sensitive and specific markers for myocardial injury in general and ACS in particular. [12][13][14][15] Immunoassays for troponin have been adapted for point-of-care testing and have been deployed in emergency departments; however, given that even the point-of-care test is of moderate complexity, not all institutions have adopted this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in the UK reported that pathology investigations are involved in 70%-80% of all health care decisions and cost the UK National Health Service (NHS) £2.5 billion (US $4 billion) annually [19]. Proper utilization of limited resources and curbing numerous unnecessary laboratory tests will help reduce health care costs because approximately 2.9%-56% of all laboratory tests are reported to be likely overutilized [20]. About 30% of the outpatient laboratory tests were found to be inappropriate and ordered just for patient check-ups [21].…”
Section: Discussionmentioning
confidence: 99%
“…Thick and thin blood lms for malaria diagnosis were made for each participant and examined under the light microscope for P. falciparum following the World Health Organization [14] procedure. Serum for ELISA assay was obtained by dispensing the blood into plain tube, allowed to clot and the serum separated [2]. Malaria parasite density MPD (Parasite per μl of blood) was calculated using the formula: Parasites per μl = number of parasites x 8000/number of leucocytes.…”
Section: Sampling and Analysesmentioning
confidence: 99%
“…Available evidence indicates that the various stages of the malaria parasite life cycle elicit immune responses [1,2]. The pro-in ammatory cytokines tend to play an important role in preventing malaria and killing the parasites.…”
Section: Introductionmentioning
confidence: 99%